Effect of certain physical and chemical factors on the development of biofilms in Lactobacillus plantarum (NTU Journal of Agriculture and Veterinary Science, 2024)
Lactobacillus plantarum is known to produce biofilms and planktonic cells. It has the ability to grow in MRS broth on inert surfaces. This study aimed to examine the ability of L. plantarum to generate biofilms and planktonic cells under diverse environmental conditions. The study also included the effect of temperature and pH changes on the growth of biofilms. In addition, the study investigated the effect of different sugars added to the MRS medium on biofilm formation. The results confirmed that the optimal temperature for biofilm growth is 37°C, and that the best pH 8. It was noted that the use of  MacConkey's medium hinders bacterial growth.. Conversely, the addition of sugars to media environments significantly enhances biofilm formation, with biofilm production increasing alongside concentrations of glucose, sucrose, fructose, maltose and starch. The production of biofilms by L. plantarum holds importance for food processing and preservation, and presents diverse potential medical applications.